Electronically Controllable Voltage-mode Multifunction Biquad Filter with High-Input and Low-Output Impedance for Biomedical Signal Processing - Jaikla, Winai (My University, 2024)
This paper presents an analog active secondorder filter providing five various voltage-mode filtering responses. The utilization of the voltage differencing differential input buffered amplifier (VD-DIBA) is a key active element. The category of the presented multifunction biquad filter is a three-input, single-output (TISO) topology. The proposed filter consists of two VD-DIBAs, together with two passive resistors and two passive capacitors that are connected to the ground. Within the same topology, the proposed configuration can offer five multiple filtering functions, including two inverting responses, namely band-pass (BP) and low-pass (LP), as well as three non-inverting responses, specifically band-stop (BS), high-pass (HP), and all-pass (AP). The high impedance characteristic shows up at all three input voltage nodes. Also, the proposed voltage-mode biquad filter exhibits high impedance at the output voltage node. This characteristic facilitates seamless integration with other circuits, eliminating the need for additional voltage buffers. The adjustment of the natural frequency (ω0) and the quality factor (Q) can be done independently. Furthermore, the ω0 parameter is under electronic and linear control while ensuring the preservation of the quality factor. To verify the potential benefits of the presented voltage-mode multifunction biquad filter, a simulation and testing process is conducted using the Pspice program and VD-DIBA, which is constructed using commercially available integrated circuits.
Keywords: Biquad filter; Commercially Available Integrated Circuit; Multifunction Filter; VD-DIBA